1988
DOI: 10.1037/0022-0167.35.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Relation between coping strategies and distress, stress, and marital adjustment of multiple-role women.

Abstract: This study examined time-management and self-care coping techniques that multiple-role women use and their relation to self-reported levels of distress, stress, and marital adjustment. The subjects (JV = 69) were married, had at least one child under the age of 12, and were employed outside the home for more than 20 hr per week. Subjects completed a demographic questionnaire, the Brief Symptom Inventory, the Derogatis Stress Profile, and the Locke-Wallace Marital Adjustment Test. In addition, subjects particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
(19 reference statements)
1
20
0
Order By: Relevance
“…Even with the changing societal trends and expectations, it is still 'expected' that working females should assume the traditional role of a homemaker (Noor, 1999;Nair, 2011). The added elements of motherhood in some working females increased the possibility of acute dual-role or multiple role stress as a mother, employee and spouse or partner (Kline & Snow, 1994;McLaughlin et al, 1988;Meleis & Stevens, 1992;O'Neill & Zeichner, 1985;Snow et al, 2003). Noor's (1999) preliminary findings on Malaysian working women's roles and wellbeing showed that the juggle between work and family demands have contributed to the adverse psychological and emotional wellbeing for the working mothers, this includes feelings of guilt, anxiety or decreased role satisfaction at work and home.…”
Section: Stress and Mothersmentioning
confidence: 99%
“…Even with the changing societal trends and expectations, it is still 'expected' that working females should assume the traditional role of a homemaker (Noor, 1999;Nair, 2011). The added elements of motherhood in some working females increased the possibility of acute dual-role or multiple role stress as a mother, employee and spouse or partner (Kline & Snow, 1994;McLaughlin et al, 1988;Meleis & Stevens, 1992;O'Neill & Zeichner, 1985;Snow et al, 2003). Noor's (1999) preliminary findings on Malaysian working women's roles and wellbeing showed that the juggle between work and family demands have contributed to the adverse psychological and emotional wellbeing for the working mothers, this includes feelings of guilt, anxiety or decreased role satisfaction at work and home.…”
Section: Stress and Mothersmentioning
confidence: 99%
“…Reliability scores may be lower with first generation immigrants as they are likely to be less acculturated than is their children's generation. The researcher also hypothesized that perceptions of marital adjustment would differ based on the partners' gender, as supported by previous research (McLaughlin et al 1988). The study sought to examine four related research questions:…”
Section: Present Studymentioning
confidence: 95%
“…Work-life research and theoretical literature form the foundation of MWP. The outcome goals and intervention areas stem from research on the association of work-life coping strategies with the well-being of workers (Anderson & Leslie, 1991;Doumas, Margolin, & John, 2003;Haddock, Zimmerman, Ziemba, & Current, 2001;McLaughlin, Cormier, & Cormier, 1988).…”
Section: Program Designmentioning
confidence: 99%
“…Organizational skills. Organizational skills can help working parents manage multiple role demands (Kater, 1985;McLaughlin et al, 1988;Paden & Buehler, 1995). Some examples include planning ahead, prioritizing tasks, and using calendars.…”
Section: Intervention Domainsmentioning
confidence: 99%